2002
DOI: 10.1016/s0043-1648(01)00856-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environment on the tribological behavior of Si-incorporated diamond-like carbon films

Abstract: An experimental study was performed to discover the effect of environment on the tribological behavior of Si-incorporated diamond-like carbon (Si-DLC) film slid against a steel ball. The films were deposited on Si (1 0 0) wafers by a radio frequency glow discharge of mixtures of benzene and dilute silane gases. Experiments using a ball-on-disk test-rig were performed in vacuum, dry air and ambient air. It was observed that coefficient of friction decreased as the environment changed from vacuum to dry air. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(27 citation statements)
references
References 13 publications
2
25
0
Order By: Relevance
“…On the other hand, the wear of films usually depended on the environment; the film wear in air was clearly larger than that in water. Previously, some researchers have reported that the addition of Si to the DLC film reduced the sensitivity of friction and wear to humidity in the environment [13][14][15][16][17]. The friction behavior of Si-DLC in our study suggests that Si addition does reduce the effect of a water environment on the friction.…”
Section: Discussionsupporting
confidence: 59%
“…On the other hand, the wear of films usually depended on the environment; the film wear in air was clearly larger than that in water. Previously, some researchers have reported that the addition of Si to the DLC film reduced the sensitivity of friction and wear to humidity in the environment [13][14][15][16][17]. The friction behavior of Si-DLC in our study suggests that Si addition does reduce the effect of a water environment on the friction.…”
Section: Discussionsupporting
confidence: 59%
“…As the ambient condition encompassed a large percentage of water, hence physisorption of water molecules led to oxidation of DLN surface [28]. Due to this oxidation of the outer most surface, the bonding strength with immediately beneath layer becomes weaker.…”
Section: Wear and Friction Characterizationmentioning
confidence: 99%
“…3 and 4d. However, under humid conditions, the chemical reaction between the film surface and ball surface should be considered to be a main parameter that governs the tribological behavior [17]. Figure 6 shows optical images of the wear scar for DLC films and 10-set alternating-layered films under three humid conditions, dry, 50% and 90% RH.…”
Section: Tribological Behaviors In Various Environmentmentioning
confidence: 99%